Breathing under water : spirituality and the twelve steps - Rohr, Richard (London SPCK, 2016)
The Twelve Steps of Alcoholics Anonymous is America's most significant and authentic contribution to the history of spirituality, says Richard Rohr. He makes a case that the Twelve Steps relate well to Christian teaching and can rescue people who are drowning in addiction and may not even realize it. To survive the tidal wave of compulsive behavior and addiction, Christians must learn to breathe under water and discover God s love and compassion. In this exploration of Twelve Step spirituality, Rohr identifies the Christian principles in the Twelve Steps, connecting The Big Book of Alcoholics Anonymous with the gospel. He draws on talks he has given for over twenty years to people in recovery and those who counsel and live with people with addictive behavior. Rohr offers encouragement for becoming interiorly alive and inspiration for making one s life manageable for dealing with the codependence and dysfunction (sin) rampant in our society.
Powerlessness -- Desperate desiring -- Sweet surrender -- A good lamp -- Accountability IS sustainability -- The chicken or the egg : which comes first? -- Why do we need to ask? -- Payback time -- Skillful means -- Is this overkill? -- An alternative mind -- What comes around must go around -- Only a suffering God can save.
Includes bibliographical references (p. 133-134) and index.
Keywords: Twelve-step programs -- Religious aspects -- Christianity